Exploring Receipt of HIV PEP Counseling Among Women Sexually Assaulted by an Intimate Partner - Du Mont, Janice (Open AIDS J, 2018)
Among 136 women sexually assaulted by a current or former male intimate partner presenting to hospital-based violence treatment centers, 58 (42.6%) received HIV post-exposure prophylaxis (HIV PEP) counseling by a specially trained sexual assault nurse. We identified factors that were associated with receipt of HIV PEP counseling. Those who received counseling were more likely to have been younger than 25 years of age, single, a student, vaginally penetrated, and have received various other services (e.g., STI prophylaxis). They were less likely to have been unemployed. Hospital-based violence treatment centers need to be aware that not all women sexually assaulted by an intimate partner will have the same risk of acquisition of HIV and care needs.